The Phenomenology and Neurobiology of Visual Distortions and Hallucinations in Schizophrenia: An Update - Silverstein, Steven M.; Lai, Adriann (Frontiers in Psychiatry, 2021)
Schizophrenia is characterized by visual distortions in approximately 60% of cases, and visual hallucinations in approximately 25-50% of cases, depending on the sample. These symptoms have received relatively little attention in the literature, perhaps due to the higher rate of auditory vs. visual hallucinations in psychotic disorders, which is the reverse of what is found in other neuropsychiatric conditions. Given the clinical significance of these perceptual disturbances, our aim is to help address this gap by updating and expanding upon prior reviews. Specifically, we: 1) present findings on the nature and frequency of visual hallucinations and distortions in schizophrenia; 2) review potential mechanisms underlying these experiences; 3) review the relationship between these visual perceptual anomalies and visual processing impairments; and 4) integrate findings across biological and psychological levels to propose an updated model of VH mechanisms, including how their content is determined, and how they may reflect vulnerabilities in the maintenance of a sense of self. In particular, we emphasize the potential role of alterations at multiple points in the visual pathway, including the retina, the roles of multiple neurotransmitters, and the role of a combination of disinhibited default mode network activity and enhanced state-related apical/contextual drive in determining the onset and content of VH. In short, our goal is to cast a fresh light on the under-studied symptoms of visual hallucinations and visual distortions in schizophrenia for the purposes of informing future work on mechanisms and the development of targeted therapeutic interventions.